CD20-positive multiple myeloma: can conventional chemotherapy still be used to achieve ideal outcome for these patients?. Issue 2 (1st February 2016) - Huang, Beihui; Li, Juan; Liu, Junru; Gu, Jingli
Abstract : In order to ascertain clinical characteristics and outcomes of CD20 + multiple myeloma (MM) patients, we retrospectively analyzed 331 newly diagnosed patients with multiple myeloma in our center. The clinical characteristics, cell morphology, immunophenotype, and cytogenetic were different between the CD20 + and CD20 − group. The median course of treatment to < nCR (near complete recovery) were 4.5 in the CD20+ group and 2 in the CD20 − group. Excluding the IgD type, overall survival (OS) and progression-free survival (PFS) in the CD20 + group were higher than that in the CD20 − group. There were no statistically significant differences in PFS and OS in CD20+ patients after treatment with conventional regimens, novel drugs ± transplant, nor statistical significance between those with the response < nCR and < nCR after treatment. In conclusion, CD20-positive myeloma cells are a cluster with heterogenous clinical characteristics, cell morphology, immunophenotype and cytogenetics. For these non-IgD CD20 + MM patients, conventional therapy might be a choice to achieve an ideal outcome.